Effects of knocking-down HIF-la (siRNA) on vgsc expression in the aggressive human breast cancer cells (MDA-MB-231) - Hussin, Mohd Zaki (Pusat Pengajian Kesihatan, 2015)
Most breast cancer tissue contain the region with low level of oxygenic measurement or known as hypoxic region. Hypoxic region known to express large quantities of hypoxic marker, HIF-la. This hypoxic condition hinders the effectiveness of treatment but also promoting cancer aggressiveness due to transcriptional up-regulation of metastatic related genes. Metastatic in breast cancer was also known to have involved with ion channel mainly the VGCSs. In this study, it was hypothesized that HIF1 alpha regulate VGSC expression which promote in breast cancer metastasis. Therefore, this study was done to investigate the interaction between HIF-laand VGSCs particularly Navi.5, and its neonatal splicing form, nNavl.5 in breast cancer cells using siRNA in MDA-MB 231 cell line. siRNA was conducted to knock-down HIF-la and the mRNA expression level of HIF-la, Nav 1.5 and nNavl.5 were measured using real-time PCR. When HIF-la was knock-downed with the siRNA, the expression of Navi.5 and nNav 1.5 was reduce by 11%. The -30% and result conclude the possible relationship between HIF-la and VGSCs mainly Navi.5 and nNavl.5 in MDA-MB 231 breast cancer cells. Hence, by understanding the involvement of HIF-la VGSCs mainly Navi.5 and nNavl.5 could promise useful information in breast cancer metastasis.